Analysis of Economic Inequality Middle Sulawesi Province 2015-2019 - Andi Herman Jaya (Institute of Computer Science (IOCS), 2021)
This study aims to determine the economic level in Central Sulawesi Province. This study uses secondary data and then analyzed using the Williamson Index analysis tool. The Williamson Index increased between districts/cities in general, increasing from 2015 which was 0.5 to 0.65 in 2019, with high levels because the Williamson Index coefficient is getting further from zero and closer to one. The regional government of Central Sulawesi Province in carrying out its activities is to prioritize areas that are lagging behind in development without the development of advanced regions, the development of equitable distribution of development results